Passive acoustic monitoring of an elusive rail, the corncrake (Crex crex): Calling patterns, detectability and monitoring recommendations - Andrea Parisi; Marie Greaney; John Carey; James Moran; Joanne O’Brien (Global Ecology and Conservation)
Due to their elusive nature, some species are hard to survey. This can present challenges for conserving rare and vulnerable species. However, conservation projects need reliable population data to understand the species status and prioritise strategies. We acoustically monitored the corncrake (Crex crex), a nationally endangered ground-nesting bird in Ireland. Little is known about the calling pattern of this species, and consequently, survey efforts may not be efficiently allocated. Twelve long-term acoustic deployments were manually scanned to extract the male broadcast calls. The calling activity was modelled as a response variable predicted by weather, lunar and temporal variables. Additionally, detectability according to weather variables and lunar fraction was assessed using a single-species occupancy model. We found marked vocal diel (hour, P < 0.001) and seasonal (date, P < 0.001) patterns. The calling activity was also negatively affected by temperature (P < 0.001) and wind speed (P < 0.001). Furthermore, a significant interaction (P = 0.023) existed between cloud cover and lunar illumination. The detectability analysis highlighted a 64 % probability of detecting a corncrake at an occupied site during a night visit. Wind speed and cloud cover negatively affected the likelihood of detection, while lunar fraction had a positive influence. We concluded that corncrake surveys should continue to focus the effort between 23:00 and 03:00, considering that calling peak activity occurred between 01:00–02:00 in May and June. Cool nights with clear sky, high lunar illumination and wind speed below 20 km/h are recommended to improve detections. By planning surveys on these conditions, conservation projects may enhance species detection and save resources required for field efforts.